Studi Sosio – Historis Terhadap Fenomena Gereja Komunitas Berdasarkan Kisah Para Rasul 2:41-47 - Hesky A. Wauran; Stimson Hutagalung; Rolyana Ferinia (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The church is a the gathering of believers who walk together in conveying the mission of the message to the world. In fulfilling this vocation mission the church has a method that moves and grows. This growth is due to the methods and ways of translating the mission of the church. Community church is one method for fulfilling the church's mission. A church community that tries to convey its mission in a way that is out of the ordinary that takes place in the main church, both from the liturgical and media delivery point of view, is typical of the community church itself. In the Bible itself, the community church played an important role in the development of Christianity. The movement that started in Jerusalem as recorded in Acts 2:41-47 is an example of the community church movement. By using a qualitative method through collecting data from primary sources, namely the Bible and also references regarding the growth of the church, both books and journal manuscripts. It is hoped that this research will be able to provide information about one method of church growth, namely a community church that seeks to convey its mission along with the development of the times.